Euro Area Sovereign Risk During the Crisis - Zoli, Edda; Sgherri, Silvia; International Monetary Fund. European Dept (IMF Working Papers; Working Paper, 2009)
While the use of public resources is critical to cushion the impact of the financial crisis on the euro-area economy, it is key that the entailed fiscal costs not be seen by markets as undermining fiscal sustainability. From this perspective, to what extent do movements in euro area sovereign spreads reflect country-specific solvency concerns? In line with previous studies, the paper suggests that euro area sovereign risk premium differentials tend to comove over time and are mainly driven by a common time-varying factor, mimicking global risk repricing. Since October 2008, however, there is evidence that markets have become progressively more concerned about the potential fiscal implications of national financial sectors' frailty and future debt dynamics. The liquidity of sovereign bond markets still seems to play a significant (albeit fairly limited) role in explaining changes in euro area spreads.
Keywords: Global Financial Crisis, 2008-2009; Financial crises : European Union countries : Econometric models; Risk management : European Union countries : Econometric models; Finance: General; Financial Risk Management; Investments: General; Investments: Bonds; Industries: Financial Services; General Financial Markets: General (includes Measurement and Data); Investment; Capital; Intangible Capital; Capacity; Financial Crises; Financial Institutions and Services: General; Investment & securities; Macroeconomics; Finance; Economic & financial crises & disasters; Sovereign bonds; Return on investment; Securities markets; Financial crises; Financial sector; Bonds; Saving and investment; Capital market; Financial services industry; Ireland